Sustainability modelling of ecommerce for rural community: A case from long lamai Ezommerce initiative - WaiShiang, Cheah; Azman, Bujang Masli; Edwin, Mit (2013)
eCommerce is able to improve the visibility and economy of rural community. However, it is a challenge to promote the eCommerce to a wider rural community. One reason is that there is a lack of understanding of the notion of sustainability in the deployment of this technology. Sustainability is always an important property in all kind of technology deployment for rural community. Questions like; How to sustain certain projects once the funding is finished? Who will pay for the project after that? Does the project still exist after certain time? This paper presents an initial sustainability model to support the eCommerce project for Long Lamai community. The model is based on the early management in eCommerce project for Long Lamai. In this paper, we first present the factors that influence the sustainability of eCommerce for the community. This is followed by the modeling of those factors using agentoriented modeling. Finally, we validate the model through the eCommerce project refinement. The model has been shown to be valueable in order to understand the community well and to strategize the eCommerce deployment for the community in a sustainable way. The contributions of this paper is the theoretical framework of the sustainability model as well as its practicality in supporting rural community projects.